Voltage and frequency monitoring based on micro controller PIC16F877A and fuzzy logic on low voltage line system - Ahmed, Shouket Abdulrahman (School of Electrical System Engineering, Universiti Malaysia Perlis, 2017)
The main objective of this project is to design, simulate and construct a monitoring system based on microcontroller to achieve the following ; to monitor the predetermined voltage level in the consumer line through detecting the voltage by using embedded microcontroller pic16F877A. when the voltage level exceeds either up or down the limit, here up 4V or down 3.7V OR up 240V or down 220V the MCU would take decision to consider this fluctuated line as failure line and then act accordingly to cut it off ; to cut off the consumer voltage line when the voltage exceeds the boundaries of a predetermined level set earlier, in this project the limit voltage level is 3.7V - 4V or 220V-240V and to replace the faulted line by another active standby line set earlier for this purpose in order to maintain the current to flow to the load without interruption or delay ; to develop an expert system to detect voltage and frequency fluctuation based on fuzzy logic (FL).